THE METRICS : ISLAND BASED DISASTER RESILIENCE - Regan Potangaroa (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2016)
HABITAT III is designed to set “a New Urban Agenda‟ for the 21st Century”. However, how that agenda is „metricated‟ will be paramount for it to have the reach and impact that it seeks. The common approach is to set a series of goals or targets to which Nations feel comfortable but it is often left as „interpretive‟ as to whether projects and programs succeeded in reality. The assumption is that there is no metrication that can cross between different programs, different cultures, different locations and different politically contexts. It is problematic. This paper looks at recent work from Fiji following cyclone Winston that underlines this problematic nature while also suggesting a way to address it. That suggestion is to use a Quality of Life metric and that Agendas like the New Urban need to carefully and deliberately incorporate such a metric so that the outcomes across the framework can be ascertained and readily compared for progress to be achieved.